TAKHRIJ HADITS TENTANG ANGGOTA BADAN YANG DIDAHULUKAN KETIKA SUJUD MELALUI ENSIKLOPEDI HADITS DAN IMPLIKASINYA DALAM PEMBELAJARAN PAI - Nandang Dwi Antoro; Afifah Ress Syahida; Nur Qomaryatul Falah; Asti Eka Wulandari; Muhammad Rizal Fadhillah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2026)
Hadith serves as the second foundational source of Islamic law after the Qur'an, yet scholarly disagreements persist regarding specific acts of worship, including the correct sequence of body parts to place on the ground during prostration in prayer. This study aims to trace and verify hadiths related to the body part sequence during prostration using a digital hadith encyclopedia application, to assess the chain of narration and textual content of the relevant hadiths, and to explore how digital hadith tools can be integrated into Islamic religious education at the school level. A descriptive-qualitative approach grounded in library research was employed, drawing on primary data from the Hadith Encyclopedia application developed by Lidwa Pusaka and supplementary data from academic journals and scholarly literature. Furthermore, the integration of digital hadith tools in Islamic religious education enhances students’ digital literacy, deepens their understanding of hadith sciences, and fosters critical thinking skills.